MODERN PRINCIPLES IN SURGERY OF INJURIES AND DISEASES OF THE SPINE - V. V. Krylov; A. A. Grin; A. K. Kaykov; S. K. Oschepkov; I. S. Lvov (Неотложная медицинская помощь)
ABSTRACT. This article describes the current trends concerning diagnostics and treatment of spinal trauma as well as tumors and diseases of vertebra column and spinal cord. The assessment of computer tomography and magnetic resonance imaging capabilities to reveal various pathologies of vertebra column and spinal cord is given. The clinical cases of usage the minimally invasive, endoscopic and transcutaneous technologies for treatment of various spinal pathologies are presented.